Financial accounting estimates through statistical sampling by computer - Newman, Maurice S. (New York : Wiley, 1976)
This book has been undertaken to fulfil three purpose of interest to professionals in the areas of management, finance, accounting, data processing, and statistics. The primary purpose is to show how statistical sampling can be used to produce satisfactory estimates for financial and accounting needs.
"A Wiley-Interscience publication."
Second ed. published under title: Accounting estimates by computer sampling.
Includes index.
Includes bibliographical references p. 225-226 and index.
hza 30/08/2018
Loans
Keywords: Accounting; Sampling (Statistics)